HMG-CoA Lyase Deficiency: A Retrospective Study of 62 Saudi Patients - Alfadhel, Majid; Abadel, Basma; Almaghthawi, Hind; Umair, Muhammad; Rahbeeni, Zuhair; Faqeih, Eissa; Almannai, Mohammed; Alasmari, Ali; Saleh, Mohammed; Eyaid, Wafaa; Alfares, Ahmed; Al Mutairi, Fuad (Frontiers in Genetics, 2022)
3-Hydroxy-3-methylglutaryl-coenzyme A lyase deficiency (HMG-CoA lyase) is a rare inborn error of leucine degradation and ketone body synthesis, caused by homozygous or compound heterozygous disease-causing variants in HMGCL. To understand the natural history of this disease, we reviewed the biochemical, clinical, and molecular data of 62 patients from 54 different families with confirmed HMG-CoA lyase deficiency (HMGCLD) diagnosis from Saudi Arabia. The majority of the affected individuals were symptomatic. At initial diagnosis, 38 patients (61.29%) presented with hypoglycemia and 49 patients (79.03%) developed metabolic acidosis. In 27 patients (43.54%), the disorder manifested in the neonatal period, mostly within the first days of life, while 35 (56.45%) patients were diagnosed within the first year of life or beyond. All the patients were alive and developed long-term neurological complications during data collection, which may significantly influence their quality of life. Common neurological findings include seizures 17/62 (27.41%), hypotonic 3/62 (4.83%), speech delay 7/62 (11.29%), hyperactivity 4/62 (4.83%), developmental delay 6/62 (9.677%), learning disability 15/62 (24.14%), and ataxic gate 1/62 (1.612%). An MRI of the brain exhibited nonspecific periventricular and deep white matter hyperintense signal changes in 16 patients (25.80%) and cerebral atrophy was found in one (1/62; 1.612%) patient. We identified a founder variant [c.122G>A; p.(Arg41Gln)] in 48 affected individuals (77.41%) in the HMGCL gene. This is the largest cohort of HMGCLD patients reported from Saudi Arabia, signifying this disorder as a likely life-threatening disease, with a high prevalence in the region. Our findings suggest that diagnosis at an early stage with careful dietary management may avoid metabolic crises.